Is the Parkland grading scale related to surgical difficulty in laparoscopic cholecystectomy? - Arguello, Gloria Guzmán; Beltran, Javier Benítez; Cruz, Israelelias Hernández; Flores, José Sevilla; Romero, Alexa; García, Brenda; Paulina, Aristeo; Pedroso, Sebastian Gomez; Herrera, Geovanna; Castellanos, Yessica (International Journal of Research in Medical Sciences, 2022)
Background: Acute cholecystitis is one of the most frequent surgical pathologies, accounting for 6-11% of patients with symptomatic gallstone disease. The gold-standard treatment for this disease is laparoscopic cholecystectomy because the minimally invasive surgery significantly benefits the patient in terms of less pain and early recovery. The Parkland grading scale (PGS) is a grading system based solely on intraoperative images, which stratifies gallbladder inflammation in five degrees based on anatomy and gallbladder inflammation. This grading system is useful and helps predict the outcome of the surgery. Methods: This study correlated the PGS with surgical difficulty based on factors such as open conversion and subtotal cholecystectomy. We included 105 patients in this study who, over a seven-month period, underwent a laparoscopic cholecystectomy and were graded by the PGS. Results: We enrolled a total of 105 patients in our study, in which 74 patients were female and 31 were male. Of the 105 patients, 94 had a laparoscopic cholecystectomy, 3 underwent an open conversion (meaning the conversion rate was 2.9%), and 8 had a subtotal cholecystectomy (a rate of 7.6%). Conclusions: The PGS is an easy and applicable grading scale for surgeons, and its application could help predict the complexity of gallbladder surgery and the outcomes of each patient. However, additional high-quality studies are needed to asses and validate this scale in patients with acute cholecystitis and determine its predictive value. We should also adjust this study depending on the surgeons’ level of expertise.